Arthroscopic Treatment of Bucket-Handle Labral Tear and Acetabular Fracture - Stabile, Kathryne J. (Elsevier, 2014)
Traumatic hip dislocations are associated with chondral and labral pathology as well as loose bodies that can be incarcerated in the joint. These types of injury often lead to traumatic arthritis. In some cases an osseo-labral fragment may become incarcerated in the joint that is not readily visualized preoperatively. In place of open surgery, hip arthroscopy permits a technique to remove loose bodies and repair labral tears to restore joint congruity and achieve fracture reduction and fixation.